Unleashing the power of Virtual Reality to manage LAZY EYE-A silent public health problem: A case study from India - Ramanathan, Vanishree; Pradhan, Keerti Bhusan; Kapoor, Smita; Tripathi, Shailesh; Bhattacharya, Sudip (Indian Journal of Community Health, 2023)
Amblyopia, also known as "lazy eye," is a childhood vision disorder characterized by impaired coordination between the brain and the eye, resulting in decreased vision in one eye. It is not caused by any structural abnormalities in the eye but rather by a lack of effective coordination between the eye and brain during the crucial period of visual development in early childhood.(1) Amblyopia is a significant global public health issue, with an estimated prevalence of 1-5% of the global population according to the World Health Organization (WHO). Developing countries face a higher burden of amblyopia due to limited access to early diagnosis and treatment. If left untreated, amblyopia can result in permanent vision loss and impairment, negatively impacting an individual's quality of life, educational achievements, and career prospects.(1) A 2017 study explored the prevalence and impact of amblyopia and strabismus in Indian children. The study found a prevalence rate of 1.67% for amblyopia among children aged 5-15 years, with a higher occurrence in rural areas compared to urban areas.(2) In another study conducted by Gupta et al. found the percentage of amblyopia was 8.6% (n=31) among 5-15 years children in uttrakhand.(3) Another study conducted by Ganekal et al. revealed the prevalence of amblyopia was 1.1% (n?=?44) among 5-15 years of students.(4) The research emphasized the importance of enhanced awareness, early detection, and improved access to suitable treatment options to alleviate the burden of amblyopia in India. Furthermore, the All India Ophthalmological Society (AIOS) conducted a study in 2019 titled "AIOS Guidelines for Amblyopia Management." This study aimed to provide evidence-based guidelines for managing amblyopia in India. It highlighted the lack of awareness and limited availability of eye care services in certain regions, leading to delayed diagnosis and treatment of amblyopia. The guidelines emphasized the significance of early screening, timely intervention, and appropriate treatment approaches to prevent long-term visual impairment in children.(5)